Negligence in Fulfilling Contractual Obligations - Sondang Sibarani, Clarisa; Elena Putri, Shabiha; Cahya Hutahaean, Triani; Gosal, Welly (Pelopor Publikasi Akademika, 2025)
This research addresses the increasing issues of breach of contract in Indonesia, particularly focusing on the legal consequences of non-compliance with debt repayment obligations and the execution of guarantees. Breach of contract, or wanprestasi, disrupts business transactions and leads to material and immaterial losses for the affected parties. The urgency of this research lies in the growing number of breach of contract cases in Indonesia, with such disputes posing significant financial and legal risks. While previous studies have explored breach of contract in broader contexts, there is limited research specifically addressing the application of Indonesian civil law in these cases, especially about debt defaults and guarantees. This study fills this gap by analyzing how Indonesian law handles breach of contract cases and the enforcement of guarantees. The research uses a mixed-method approach, combining legal analysis and case studies to examine the consequences of defaults and the protection of creditors' rights. The findings highlight the need for legal reforms to improve the enforcement of contracts and enhance creditor protection. This research contributes to understanding contract law in Indonesia, offering practical recommendations for businesses and policymakers to address breaches more effectively and ensure fairer outcomes in the judicial process.